Long-Term Outcome of Rockwood Capsular Shift for Recurrent Shoulder Dislocation. (December 2016) - Murena, Luigi; Guindani, Nicola; Turino, Stefano; Grassi, Federico A; Cherubino, Paolo
Purpose: To review the long-term outcome of Rockwood capsular shift for recurrent shoulder dislocation secondary to trauma. Methods: Records of 30 males and 4 females who underwent Rockwood capsular shift for recurrent (≥2 episodes) anterior shoulder dislocation were reviewed. An additional Bankart repair with different techniques was performed in 24 of the patients by 2 different surgeons. The outcome was assessed using the Western Ontario Shoulder Instability Index (WOSI) and the Western Ontario Osteoarthritis of the Shoulder (WOOS) index questionnaires, the modified Rowe score, and the Constant-Murley score. Shoulder range of motion (ROM) was measured. Degenerative joint changes were evaluated on radiographs. Results: During a mean follow-up of 13 (range, 10–16) years, 6 (18%) patients had a mean of 1.2 recurrent dislocations. Four of the patients reported a traumatic event during recurrent dislocation. Of the 6 patients, 3 had undergone a Bankart lesion repair. Better Rowe and adjusted Constant scores were associated with lower age at first dislocation, at the index surgical procedure, and at follow-up. Four patients developed glenohumeral osteoarthritis: 2 were mild or moderate and 2 were severe and symptomatic. Glenohumeral osteoarthritis was associated with follow-up duration (p=0.03) and poorer Rowe score (p=0.012), adjusted Constant score (p=0.001), and WOOS score (p=0.006). Conclusion: Rockwood capsular shift can preserve shoulder ROM, with rates of recurrent dislocation and degenerative joint changes comparable with other techniques.